2019
DOI: 10.1021/acs.cgd.8b01556
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide:Triethanolamine Salt as a Strategy To Improve the Biopharmaceutical Properties and Photostability of the Drug

Abstract: With the purpose of enhancing the biopharmaceutical properties of the furosemide, a pharmaceutical salt was obtained and characterized by combining the drug and triethanolamine. The solid system was prepared using different techniques such as kneading, grinding, and slow evaporation. It was characterizated by X-ray powder diffraction, solid-state nuclear magnetic resonance, infrared and Raman spectroscopy, thermal analysis, and scanning electron microscopy. The results showed that the same pharmaceutical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…However, it can also be observed at 1610 cm −1 in the physical mixture of composition-TEA, where the liquid triethanolamine was added to the powder excipients, and the mixing of the compositions in a mortar led to partial salt formation. Similar results were found by Abraham et al They observed a new band at 1612 cm −1 , corresponding to the COO − group, while furosemide and triethanolamine were used for salt formation [31].…”
Section: Positron Annihilation Lifetime Spectroscopysupporting
confidence: 87%
“…However, it can also be observed at 1610 cm −1 in the physical mixture of composition-TEA, where the liquid triethanolamine was added to the powder excipients, and the mixing of the compositions in a mortar led to partial salt formation. Similar results were found by Abraham et al They observed a new band at 1612 cm −1 , corresponding to the COO − group, while furosemide and triethanolamine were used for salt formation [31].…”
Section: Positron Annihilation Lifetime Spectroscopysupporting
confidence: 87%
“…Several authors have reported pharmaceutical salts and cocrystals of FUR. A search of this dataset for drug-drug multi-component crystals revealed a total of 11 systems [8,[10][11][12][13][29][30][31]. A common structural feature observed is the key role of the carboxylic group in the interaction with the coformer or counterion and the formation of other synthons involving the sulfonamide group that participates in stabilizing the crystal structure packing.…”
Section: Coformer Selectionmentioning
confidence: 99%
“…When the two APIs are joined together in the solid form, the reported IR bands with diagnostic values are expected to be shifted, thus indicating the presence of intermolecular forces between functional groups-i.e., hydrogen bonds-which build the cocrystal structures [44]. Band assignments (Table 3) were performed based on the crystallographic analysis (Section 3.1) and considering the spectroscopic data available for related FUR compounds found in the literature [13]. FUR exhibits stretching frequencies at 3400 and 3351 cm −1 (sulfonamide primary amine), 3285 cm −1 (sulfonamide secondary amine), 1670 cm −1 (carboxyl stretch), and 1328 and 1139 cm −1 (sulfonamide S=O stretching modes).…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…), sometimes along with solubility enhancement. The triethanolamine salt of furosemide not only increased the aqueous solubility of the drug but also improved its chemical photostability …”
Section: Introductionmentioning
confidence: 99%